Attitudes toward coronavirus disease 2019 vaccination in people with multiple sclerosis. Issue 2 (April 2022) - Marrie, Ruth Ann; Dolovich, Casandra; Cutter, Gary R; Fox, Robert J.; Salter, Amber
Objective: We estimated coronavirus disease 2019 (COVID-19) vaccination rates in the North American Research Committee on Multiple Sclerosis (NARCOMS) population and investigated reasons for vaccine hesitancy. Methods: In Spring 2021, we surveyed the NARCOMS participants about COVID-19 vaccinations. Participants reported whether they had received any COVID-19 vaccination; if not, they reported why not. They also reported whether they had received influenza vaccination. Using multivariable logistic regression, we assessed participant characteristics associated with uptake of COVID-19 and influenza vaccines. Results: Of 4955 eligible respondents, 3998 (80.7%) were females with a mean (SD) age of 64.0 (9.7) years. Overall, 4165 (84.1%) reported that they had received a COVID-19 vaccine, most often Pfizer-BioNTech and Moderna, and 3723 (75.4%) received a seasonal influenza vaccine. Reasons for not getting the COVID-19 vaccine included possible adverse effects (47.73%), possible lack of efficacy (13.7%), and lack of perceived need (17.1%). Factors associated with receiving the COVID-19 vaccine included receipt of influenza vaccine, older age, higher socioeconomic status, any leisure physical activity, and use of disease-modifying therapy. Conclusion: In this older cohort of people with multiple sclerosis, COVID-19 vaccine uptake was high, exceeding uptake of seasonal influenza vaccine. Concerns regarding safety, efficacy, and lack of perceived risk were associated with not obtaining the COVID-19 vaccine.